Review of Unconventional Natural Gas Liquefaction Processes - Xu, Jingxuan; Lin, Wensheng; Chen, Xi; Zhang, Hua (Frontiers in Energy Research, 2022)
Liquefied natural gas (LNG) has become an important part in the energy industry on account of its high energy density, low carbon emission, and convenient transportation. In recent years, with the discovery of unconventional natural gas resources, the situation of the world's natural gas liquefaction plants using conventional natural gas as feedstock is changing. Unlike traditional LNG plants, the unconventional natural gas liquefaction processes require special considerations in design and manufacturing. This paper summarizes and analyzes the characteristics and differences of several typical unconventional natural gas liquefaction processes compared to traditional natural gas liquefaction processes, including coalbed methane liquefaction, synthetic natural gas liquefaction, LNG-FPSO and PLNG (Pressurized liquefied natural gas). Moreover, a state-of-the-art review of the recent progress on design and optimization of unconventional natural gas liquefaction processes is presented.